Pembuatan Snack Bar Rasa Biryani dengan Menggunakan Berbagai Jenis Pemanis Sebagai Bahan Perekat - Shi Shi Irgita Alamsyah; Lilis Sulandari; Any Sutiadiningsih; Mauren Gita Miranti (Pusat Riset dan Inovasi Nasional, 2024)
Snack bars are snacks consisting of ingredients such as cereals, fruits and sometimes nuts that are glued together with adhesives. The adhesive material has the function of providing a solid and sturdy texture so as to produce the desired characteristics of the snack bar. The adhesive material used in making snack bars is sugar or sweetener. This study aims to determine how the organoleptic quality and nutritional content of snack bars using various types of sweeteners (glucose syrup, High Fructose Syrup (HFS), and honey) as an adhesive material. This type of research is experimental with observational data collection through organoleptic quality assessment and nutritional content of biryani flavored snack bars. The results showed that the snack bar with High Fructose Syrup (HFS) produced the best snack bar organoleptic quality, perfect block-shaped snack bar; solid and not hollow; slightly brown yellow color; biryani aroma; crunchy texture and easy to break; and balanced sweet and biryani taste; Laboratory analysis showed that biryani-flavored snack bar has nutritional content in the form of calories of 285.80 kcal/100g, with carbohydrate content of 69.24%, protein of 15.40%, fat of 3.24%, moisture content of 10.90% and ash content of 1.22%.